Optimization of Community Satisfaction Index Measurement Instruments at the Surakarta City Population and Civil Registration Office based on the level of community understanding - Ningsih, Yuliana Ristantya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Government agencies/institutions that provide public services must conduct community satisfaction surveys to measure the quality of their services. This obligation is also attached to the Population and Registration Office throughout Indonesia. This research aims to find out how the public understands the SKM instrument used by the Surakarta City Population and Civil Registration Office and to provide recommendations on optimizing the IKM measurement instrument of the Surakarta City Population and Civil Registration Office. The method used in this research is descriptive qualitative with the research subject are the people of Surakarta City. The results showed that the level of public understanding of the SKM Dukcapil instrument was good. However, it is still necessary to optimize/refine the SKM instrument by adding information to make it easier for people to understand the 9 SKM indicator questions